2004
DOI: 10.1111/j.1572-0241.2004.04151.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome in an Open Label, Therapeutic Trial of High-Dose Omeprazole in Laryngitis

Abstract: In a carefully defined population of patients with laryngitis (a) 63% have a laryngoscopic response to 3 months of potent acid suppression without significant improvement in laryngeal symptoms; (b) neither voice measures, esophageal acid exposure time, symptoms nor severity of laryngitis predict outcome; and (c) although numbers were small, all patients with a positive pharyngeal pH study responded to therapy and pharyngeal pH-metry may prove useful; (4) available evidence supports an empiric trial of high-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 29 publications
3
84
0
8
Order By: Relevance
“…Reflü içeriğinin hipofarenkse ulaşması ile salınan sitokinler mukozada enflamasyon, ödem, eritem ile larengeal belirtilere ve hırıltıya yol açtığı, ayrıca nazofarengeyal enflamasyonun östaki tüpünde obstruksiyona yol açarak otit sıklığını artırdığı öne sürülmüştür (11)(12)(13).…”
Section: Rġsk Faktörlerġ Ve Patofġzyolojġunclassified
“…Reflü içeriğinin hipofarenkse ulaşması ile salınan sitokinler mukozada enflamasyon, ödem, eritem ile larengeal belirtilere ve hırıltıya yol açtığı, ayrıca nazofarengeyal enflamasyonun östaki tüpünde obstruksiyona yol açarak otit sıklığını artırdığı öne sürülmüştür (11)(12)(13).…”
Section: Rġsk Faktörlerġ Ve Patofġzyolojġunclassified
“…Proximal oesophageal and hypopharyngeal pH testing are not widely available and are considered less useful by both community and academic gastroenterologists (Ahmed et al 2006), and there is a lack of consensus on how much refl ux in the hypopharynx is normal. Most studies show that hypopharyngeal pH-monitoring is not a predictor of response to acid inhibitory therapy as response to therapy is no more likely in individuals with abnormal hypopharyngeal acid refl ux compared to individuals with no acid refl ux (El-Serag et al 2001;Noordzij et al 2001;Vaezi et al 2003;Williams et al 2004;Vaezi et al 2006;Wo et al 2006). Finally it should be taken into account that oesophageal pH-monitoring is not even a perfect gold standard test for GERD.…”
Section: Reimer and Bytzermentioning
confidence: 99%
“…Various modifi cations of the Laryngeal Symptom Score (LSS) have been used in some studies (Williams et al 2004;Wo et al 2006;Qua et al 2007). The frequency and severity of a number (usually up to 6) of LPR symptoms are assessed over the preceding week to give a cumulative score.…”
Section: Patient Reported Outcomes In Laryngopharyngeal Refl Uxmentioning
confidence: 99%
“…Chronic cough, hoarseness, sinusitis, chronic otitis media, erythema in the larynx, a cobblestone appearance, reaching of the reflux content to hypopharynx, the release of cytokines and associated with this laryngeal symptoms, such as mucosal inflammation, edema, erythema, and stridor appear. Moreover, it is suggested that nasopharyngeal inflammation leads to an increase in otitis media by causing obstruction in the Eustachian tube (16)(17)(18).…”
Section: Clinical Featuresmentioning
confidence: 99%